Risk-of-Malignancy Index in preoperative evaluation of clinically restricted ovarian cancer - Torres, José Carlos Campos; Derchain, Sophie Françoise Mauricette; Faúndes, Aníbal; Gontijo, Renata Clementino; Martinez, Edson Zangiacomi; Andrade, Liliana Aparecida Lucci de Ângelo (São Paulo Medical Journal, 2002)
CONTEXT: There is no adequate preoperative method for differentiating between benign and malignant pelvic masses. Evaluations of CA 125 serum levels, ultrasonography findings and menstrual state have been tested in isolation as diagnostic methods. The evaluation of these three methods in association with each other could improve diagnostic performance. OBJECTIVE: To evaluate the risk-of-malignancy index by combining serum CA 125 levels, ultrasound score and menopausal status in preoperative diagnoses for women with pelvic masses clinically restricted to the ovaries and without clear evidence of malignancy. DESIGN: Cross-sectional study. SETTING: Centro de Atenção Integral à Saúde da Mulher, Universidade Estadual de Campinas, Campinas, São Paulo, Brazil. PARTICIPANTS: 158 women admitted between January 1996 and March 1998 for surgical exploration of pelvic masses. PROCEDURES: The risk-of-malignancy index was calculated as US x M x CA 125, performed preoperatively. Ultrasound findings were classified according to the shape, size, multiplicity, presence of wall expansion involvement or ascites, using a score system (US). Menopausal status was considered as 1 for premenopausal and 3 for postmenopausal (M), and CA 125 serum levels were considered in absolute values. STATISTICAL ANALYSIS: Most relevant variables were included in a logistic multiple regression model, fitted using the ultrasound score, the serum CA 125 level and the menopausal status. The model was used for evaluating the performance of each individual predictor in determining the malignancy of these tumors and identifying the risk-of-malignancy index. RESULTS: The best individual performance was found in CA 125 levels (sensitivity of 78%, specificity of 75%), followed by ultrasound score (sensitivity of 75%, specificity of 73%) and menopausal status (sensitivity of 73%, specificity of 69%). The performance obtained for the risk-of-malignancy index at the cut-off point of 150 was a sensitivity and specificity of 79%. The area under the ROC curve for the risk-of-malignancy index was 0.90, which was greater than the area for CA 125 levels (0.83) or ultrasound score (0.79). CONCLUSION: The risk-of-malignancy index using ultrasound morphological score, serum CA 125 levels and menopausal status might be of value in the preoperative assessment of ovarian carcinomas.